2016
DOI: 10.1186/s12865-016-0143-2
|View full text |Cite
|
Sign up to set email alerts
|

TIRF imaging of Fc gamma receptor microclusters dynamics and signaling on macrophages during frustrated phagocytosis

Abstract: BackgroundRecent evidence indicates that in addition to the T-cell receptor, microclustering is an important mechanism for the activation of the B-cell receptor and the mast cell Fcε-receptor. In macrophages and neutrophils, particles opsonized with immunoglobulin G (IgG) antibodies activate the phagocytic Fcγ-receptor (FcγR) leading to rearrangements of the actin cytoskeleton. The purpose of this study was to establish a system for high-resolution imaging of FcγR microclustering dynamics and the recruitment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 37 publications
6
28
0
Order By: Relevance
“…We tested whether these myosin 1-actin puncta were associated with FcR clusters by transfecting cells with EGFP-FcgRIIA. As has been previously observed, macrophages spreading on IgG formed discrete FcR clusters 41,42 . We found that myo1f and FcgRIIA distinctly colocalized at these structures ( Fig.…”
Section: Myo1e and Myo1f Localize To Fcr-actin Adhesions During Frustsupporting
confidence: 77%
“…We tested whether these myosin 1-actin puncta were associated with FcR clusters by transfecting cells with EGFP-FcgRIIA. As has been previously observed, macrophages spreading on IgG formed discrete FcR clusters 41,42 . We found that myo1f and FcgRIIA distinctly colocalized at these structures ( Fig.…”
Section: Myo1e and Myo1f Localize To Fcr-actin Adhesions During Frustsupporting
confidence: 77%
“…CD14 is one of the most common phagocytic receptors on the surface of macrophages, which is the coreceptor for LPS and can mediate the innate immune response to LPS via MyD88, TIRAP, and TRAF6 . CD64 is one member of the Fc gamma receptor (FcγR) family, which can activate the phagocytosis through recognizing bacteria and viruses opsonized by IgG …”
Section: Discussionmentioning
confidence: 99%
“…Following phagocyte contact with IgG-coated surfaces or on supported lipid bilayers, formation of FcγRII nanoclusters suggests activation-driven organization of receptor redistribution ( 75 ). FcγR clusters are localized in front of ruffles on extending pseudopods, with rapid recruitment of Syk to advancing pseudopods and subsequent retrograde movement toward the cell center ( 76 ). PI3K co-localized with actin around FcγR clusters, suggestive of signal propagation from FcγR and consistent with PI3K-dependent control of actin cytoskeletal rearrangements ( 76 ).…”
Section: Molecular Segregation and The Formation Of A Phagocytic “Synmentioning
confidence: 99%
“…FcγR clusters are localized in front of ruffles on extending pseudopods, with rapid recruitment of Syk to advancing pseudopods and subsequent retrograde movement toward the cell center ( 76 ). PI3K co-localized with actin around FcγR clusters, suggestive of signal propagation from FcγR and consistent with PI3K-dependent control of actin cytoskeletal rearrangements ( 76 ).…”
Section: Molecular Segregation and The Formation Of A Phagocytic “Synmentioning
confidence: 99%